Clinical and serological characteristics of type 3 APS, isolated T1DM and LADY/LADA - Yawei Qiu; Lin Guo; Hongyan Pan; Huaqiu He; Qiang Li (BMC Endocrine Disorders)
Abstract Background There are few studies comparing Type 3 autoimmune polyendocrine syndromes (APS) with isolated type 1 diabetes mellitus (T1DM), latent autoimmune diabetes in youth (LADY), and latent autoimmune diabetes in adults (LADA) in the Chinese population. This study aims to report the clinical and serological characteristics of Chinese patients with Type 3 APS, isolated T1DM, LADY and LADA, and to make comparisons. Methods This study retrospectively analyzed the clinical and serological characteristics of hospitalized patients with Type 3 APS, T1DM, LADY and LADA who were admitted to our center. Results A total of 69 patients were included in this study, comprising 18 with Type 3 APS, 20 with T1DM, and 31 with LADY/LADA. The majority of Type 3 APS patients were female, whereas T1DM and LADY/LADA groups had a higher proportion of males. The median age and onset age of diabetes in the Type 3 APS group were 35.50 (31.00, 52.50) years and 30.50 (26.75, 47.25) years, respectively. Diabetes and autoimmune thyroid disease (AITD) in Type 3 APS patients may occur simultaneously or several years apart. The levels of GADAb and thyroid autoantibodies in Type 3 APS patients were often higher. Conclusions Type 3 APS exhibits differences when compared to isolated T1DM and LADY/LADA. For patients with TIDM or LADY/LADA, especially female patients, those over 30 years old or with high-titer GADAb, attention should be paid to screening for APS 3, including the detection of thyroid autoantibodies. Patients suspected or confirmed to have Type 3 APS need long-term follow-up. Clinical trial number Not applicable.